THE EFFECTS OF THE MN2+ IONS ON THE MORPHOLOGICAL PROPERTIES OF ZINCOXIDE THIN FILMS - Aydın, Cıhat; Orhan, Ayhan (My University, 2020)
The nanocrystalline ZnO thin films were successfully prepared via the sol-gel spin coating method for the different atomic ratios Mn doping (0.1%, 0.5%, 1%, 2%, 5%). The detailed surface analysis of samples was performed by Atomic Force Microscopy (AFM). The AFM results indicate that the ZnO films have nanostructure. The morphological characteristics of films show that Mn2+ ions are included in the crystal lattice of ZnO without changing the structure. The influence of Mn doping on film growth has resulted in an increase in fiber size and roughness. The fiber size values of the films were found to vary from 0.898 µm to 2.960 µm with Mn doping. The study revealed the possibility with Mn doping of controlling, optimizing and improving the morphology in ZnO thin-film production.
Keywords: Nanobilim ve Nanoteknoloji; Malzeme Bilimleri; Özellik ve Test; Mineraloji